Helping Dyslexic Children with GraphoGame Digital Game-Based Training Tool (An Interview) - Heikki Lyytine (Психологическая наука и образование, 2018)
Professor Heikki Lyytinen (University of Jyväskylä, Finland) recently visited the Moscow State University of Psychology & Education and gave a lecture on GraphoGame, a technology-based intervention method that he and his colleagues have developed to help children with dyslexia. The interview has been conducted by the press-service of the Moscow State University of Psychology & Education.